Temporal space infection secondary to recurrent buccal space infection from mandibular deciduous molar in 7-year-old child: a case report - Rout, Sourav; Gautam, Shailesh; Shah, Arun Kumar (Journal of Chitwan Medical College, 2019)
Head and neck space infections are usually secondary to odontogenic infections due to translocation of oral microbes to fascial space via odontogenic route resulting in progression by enzymatic degradation of connective tissue. Various factors like microbiological, host, nutritional and socioeconomic factors are responsible for progression of fascial space infection that might take fatal course if not treated in time. The present case report describes a child with fascial space infection of oral and maxillofacial region who was treated by incision and drainage in department of oral and maxillofacial surgery of this hospital. Fascial space infections are one of the surgical emergencies and need to be addressed in early stage as it has rapid regional and systemic progression leading to fatal outcome. It is multifactorial and all need to be addressed. Incision and drainage with removal of cause with antimicrobial therapy is treatment modality of space infection. Inadequate drainage might lead to recurrence of infection and progression to distant secondary spaces.